2015
DOI: 10.1097/pgp.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic Stromal Tumor of the Ovary With Mutation in Exon 3 of β-catenin

Abstract: Microcystic stromal tumor of the ovary is a very rare ovarian tumor with distinctive microcystic histologic features and a characteristic immunophenotype of stromal tumor. However, its origin, tumor pathogenesis, and prognosis have not been well established until now. We report a very unusual case of a microcystic stromal tumor of the ovary with a mutation in exon 3 of the β-catenin (CTNNB1) gene. Macroscopically, the fragmented ovarian tumor showed a diffuse solid mass. Microscopically, the tumor had a pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 7 publications
4
34
1
Order By: Relevance
“…These findings further establish that the tumorigenesis of MST involves dysregulation of the Wnt/b-catenin pathway. [2][3][4]28 b-catenin has a key role in cell-cell adhesion and binds to the cytoplasmic region of E-cadherin and acatenin at adherens junctions. 28 b-catenin also plays a critical role in the transduction of Wnt signals; in the absence of Wnt signaling, b-catenin joins a destruction complex, where it undergoes CK1a and GSK-3b phosphorylation and is subsequently degraded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings further establish that the tumorigenesis of MST involves dysregulation of the Wnt/b-catenin pathway. [2][3][4]28 b-catenin has a key role in cell-cell adhesion and binds to the cytoplasmic region of E-cadherin and acatenin at adherens junctions. 28 b-catenin also plays a critical role in the transduction of Wnt signals; in the absence of Wnt signaling, b-catenin joins a destruction complex, where it undergoes CK1a and GSK-3b phosphorylation and is subsequently degraded.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the S33C and S33P mutations found in 3 previous MSTs were not detected in any of our cases. 2,3 Of note, S37, as well as S33, are critical N-terminal GSK-3b phosphorylation sites. 28 Furthermore, the presence of diffuse cyclin D1 staining in all 15 MSTs provides indirect evidence that activation of b-catenin with upregulation of cyclin D1 may play a role in the tumorigenesis of MST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a recent study of 10 microcystic stromal tumours, we identified CTNNB1 and APC mutations in eight and two cases, respectively . Mutations in CTNNB1 and APC genes are mutually exclusive in microcystic stromal tumour and they result directly in nuclear immunoreactivity with beta‐catenin and cyclin D1 through activation of the Wnt signalling pathway . Herein, we report four ovarian neoplasms with a different morphology but an identical immunophenotype and molecular events to microcystic stromal tumour.…”
Section: Introductionmentioning
confidence: 94%